2015
DOI: 10.1016/j.envpol.2015.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the effects of hydrocarbon pollution in the Amazon forest using hyperspectral satellite images

Abstract: The global demand for fossil energy is triggering oil exploration and production projects in remote areas of the world. During the last few decades hydrocarbon production has caused pollution in the Amazon forest inflicting considerable environmental impact. Until now it is not clear how hydrocarbon pollution affects the health of the tropical forest flora. During a field campaign in polluted and pristine forest, more than 1100 leaf samples were collected and analysed for biophysical and biochemical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 67 publications
5
110
0
4
Order By: Relevance
“…Research has attributed these biochemical alterations in forest areas where oil facilities are located (Arellano et al 2015;Noomen et al 2012). Data in Table 2 shows that there is a high level of significant difference between vegetation at the SS and NSS (NDVI, SAVI, ARVI2 and G-NIR), this might suggest that vegetation at the SS responded spectrally different with the ones at the NSS.…”
Section: Effects Of Oil Spill On the Vegetation Indices At The Ss Andmentioning
confidence: 92%
See 2 more Smart Citations
“…Research has attributed these biochemical alterations in forest areas where oil facilities are located (Arellano et al 2015;Noomen et al 2012). Data in Table 2 shows that there is a high level of significant difference between vegetation at the SS and NSS (NDVI, SAVI, ARVI2 and G-NIR), this might suggest that vegetation at the SS responded spectrally different with the ones at the NSS.…”
Section: Effects Of Oil Spill On the Vegetation Indices At The Ss Andmentioning
confidence: 92%
“…Changes in mangrove canopy properties from oil spills can be diagnosed through the change in leaf spectral reflectance (Van Der Meer et al 2002). One of the important remote sensing tool used for monitoring oil affected mangroves in the study is the leaf spectral changes as an indicator for detecting vegetation impacted by the oil spills (Hoff et al 2002;Arellano et al 2015). The presence of hydrocarbons in forest sites seems to produce a change in the internal structure of the plant that results in low reflectance values and gas affected areas may also be responsible for low vegetation density (Noomen 2007).…”
Section: Vegetation Response To Oil Spillmentioning
confidence: 99%
See 1 more Smart Citation
“…Deforestation is not only limited to the pathways of these roads and pipelines, but their construction opens up what was previously inaccessible forest to illegal logging and exposes faunal populations to increased hunting pressures (Finer et al 2008). In addition to this are the risks of oil spills and wastewater damaging the peatland ecology, as observed in parts of Western Amazonia (Finer et al 2008;Arellano et al 2015).…”
Section: Mining and Hydrocarbonsmentioning
confidence: 99%
“…It has been suggested that the presence of hydrocarbons seems to produce a change in the internal structure of the plant that results in low reflectance values and oil pollution may also lead to low density of vegetation in the affected areas (Oliveira, Crosta, and Goncalves 1997). In addition, vegetation growing near leaking gas pipelines has been shown to have changes in their geobotany and reflectance (van der Meer et al 2002;Arellano et al 2015). The geobotanical anomalies were associated with the effects of oil spills and pollution on the growth of the vegetation (Noomen et al 2008).…”
Section: Introductionmentioning
confidence: 99%